The effect of annealing temperatures on the optical parameters of NiO0.99Cu0.01 thin films - Ramiz A. Mohammed Al-Ansari (Iraqi Journal of Physics, 2019)
NiO0.99Cu0.01 films have been deposited using thermal evaporation technique on glass substrates under vacuum 10-5mbar. The thickness of the films was 220nm. The as -deposited films were annealed to different annealing temperatures (373, 423, and 473) K under vacuum 10-3mbar for 1 h. The structural properties of the films were examined using X-ray diffraction (XRD). The results show that no clear diffraction peaks in the range 2θ= (20-50)o for the as deposited films. On the other hand, by annealing the films to 423K in vacuum for 1 h, a weak reflection peak attributable to cubic NiO was detected. On heating the films at 473K for 1 h, this peak was observed to be stronger. The most intense peak is at 2θ = 37.12o with the preferential orientation of the films being (111) plane. The optical properties of the films have been studied. The effect of annealing temperature on the optical parameters of NiO0.99Cu0.01 such as transmittance, reflectance, absorption coefficient, refractive index, extinction coefficient, and real and imaginary parts of dielectric constant has been reported.